O13.5 Core groups of individuals with chlamydia and/or gonorrhoea reinfections have increased odds of diagnosis with infectious syphilis: a population-based retrospective cohort study in british columbia, canada, 2006–2015. (8th July 2017) - Jiang, Heming; Lukac, Christine; Ogilvie, Gina; Gilbert, Mark; Grennan, Troy; Wong, Jason
Abstract : Introduction: The incidence of infectious syphilis (primary, secondary, or early latent) has increased in British Columbia (BC). Identifying core groups at risk for syphilis can inform public health programming. We assessed the odds of syphilis infection among individuals with repeat Chlamydia trachomatis (CT) and/or Neisseria gonorrhoeae (GC) infections in this population-based analysis. Methods: Surveillance records for all BC residents diagnosed with ≥2 CT (CT reinfection) or ≥2 GC (GC reinfection) or ≥2 infections including CT and GC (CT/GC reinfection) from 1/1/2006 to 12/31/2015 were linked with all infectious syphilis cases from the same time period. Logistic regression models were used to measure the odds of acquiring syphilis with greater number of CT and/or GC reinfections, adjusted for age, ethnicity and population (e.g., men who have sex with men). Results: Of 1 03 115 people having a CT infection, 11 458 (11.1%) had CT reinfection; of 14 713 people with a GC infection, 1514 (10.3%) had GC reinfection. Overall, 4989 individuals had CT/GC reinfection. Among these three re-infection groups (CT, GC, CT/GC), 80.9%/72.9%/63% had 2 infections, 14.4%/15.9%/19.5% had 3 infections, 3.2%/6.1%/8.9% had 4 infections and 1.6%/5.1%/8.6% had 5+ infections. Of all syphilis cases in BC, 7.4%/9.4%/12.3% were diagnosed among individuals with CT reinfection, GC reinfection and CT/GC reinfection. The odds of syphilis increased with greater number of infections, which persisted after adjustment in all three groups. Among the group with CT/GC reinfection, individuals with 3, 4 and 5+ infections had increased odds of syphilis compared to individuals with 2 infections (OR=2.2 (95%CI 1.6, 3.0), OR=2.5 (95%CI 1.7, 3.6) and OR=4.1 (95%CI 3.0, 5.7) respectively). Conclusion: Increasing number of CT and/or GC reinfections is strongly and independently associated with a syphilis diagnosis. Targeting public health interventions to a core group of individuals with CT/GC reinfections may be an effective syphilis prevention strategy.